Combination of bazedoxifene with chemotherapy and SMAC-mimetics for the treatment of colorectal cancer - Rhynelle S. Dmello; Michelle Palmieri; Pathum S. Thilakasiri; Larissa Doughty; Tracy L. Nero; Ashleigh R. Poh; Sarah Q. To; Erinna F. Lee; W. Douglas Fairlie; Lisa Mielke; Michael W. Parker; Ivan K. H. Poon; et al. (Cell Death and Disease)
Abstract Excessive STAT3 signalling via gp130, the shared receptor subunit for IL-6 and IL-11, contributes to disease progression and poor survival outcomes in patients with colorectal cancer. Here, we provide evidence that bazedoxifene inhibits tumour growth via direct interaction with the gp130 receptor to suppress IL-6 and IL-11-mediated STAT3 signalling. Additionally, bazedoxifene combined with chemotherapy synergistically reduced cell proliferation and induced apoptosis in patient-derived colon cancer organoids. We elucidated that the primary mechanism of anti-tumour activity conferred by bazedoxifene treatment occurs via pro-apoptotic responses in tumour cells. Co-treatment with bazedoxifene and the SMAC-mimetics, LCL161 or Birinapant, that target the IAP family of proteins, demonstrated increased apoptosis and reduced proliferation in colorectal cancer cells. Our findings provide evidence that bazedoxifene treatment could be combined with SMAC-mimetics and chemotherapy to enhance tumour cell apoptosis in colorectal cancer, where gp130 receptor signalling promotes tumour growth and progression.